2015
DOI: 10.1038/nmat4410
|View full text |Cite
|
Sign up to set email alerts
|

Efficient hydrogen evolution catalysis using ternary pyrite-type cobalt phosphosulphide

Abstract: The scalable and sustainable production of hydrogen fuel through water splitting demands efficient and robust Earth-abundant catalysts for the hydrogen evolution reaction (HER). Building on promising metal compounds with high HER catalytic activity, such as pyrite structure cobalt disulphide (CoS2), and substituting non-metal elements to tune the hydrogen adsorption free energy could lead to further improvements in catalytic activity. Here we present a combined theoretical and experimental study to establish t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
646
5
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,191 publications
(671 citation statements)
references
References 49 publications
19
646
5
1
Order By: Relevance
“…A small Tafel slope is desirable to drive a large current at low overpotential, and metal sulfides usually exhibit Tafel slopes ranging from 40 to 120 mV/decade. 11,[43][44][45] The enhanced catalytic capability was confirmed by the EIS results, as the Nyquist plots ( Figure S11) for the Fe x Co 1−x S 2 (x = 0.98 to 0.32) exhibited substantially reduced charge-transfer resistance (R ct ) as compared to the Fe 1.00 Co 0.00 S 2 (Figure 5c). Among the Fe x Co 1−x S 2 , the lowest R ct of 23 was obtained at x = 0.68.…”
Section: Resultsmentioning
confidence: 73%
“…A small Tafel slope is desirable to drive a large current at low overpotential, and metal sulfides usually exhibit Tafel slopes ranging from 40 to 120 mV/decade. 11,[43][44][45] The enhanced catalytic capability was confirmed by the EIS results, as the Nyquist plots ( Figure S11) for the Fe x Co 1−x S 2 (x = 0.98 to 0.32) exhibited substantially reduced charge-transfer resistance (R ct ) as compared to the Fe 1.00 Co 0.00 S 2 (Figure 5c). Among the Fe x Co 1−x S 2 , the lowest R ct of 23 was obtained at x = 0.68.…”
Section: Resultsmentioning
confidence: 73%
“…As a result, more rapid liberation of catalytically‐active sites is achieved by faster release of bubble, thus benefiting for further contact of electrolytes on the catalyst/electrode surface. Later, the same research group reported a type of ternary pyrite‐type cobalt phosphosulphide (CoPS) nanowires as a highly efficient catalyst for both electrochemical and photoelectrochemical hydrogen evolution 52. By combining with a theoretical study, it was shown that the CoPS nanowire electrodes presented a geometrical current density of 10 mA cm –2 at a low overpotential of 48 mV vs. RHE.…”
Section: Hermentioning
confidence: 99%
“…Hydrogen has been referred as fuel of future with water as an oxidation product, no carbon and higher enthalpy of combustion than any other chemical fuel 1, 2, 3. Although extensive research has been carried out to produce the hydrogen fuel, still sustainable production of hydrogen is a great challenge 4.…”
Section: Introductionmentioning
confidence: 99%